Language maintenance and shift - Pauwels, Anne (Cambridge : Cambridge University Press, 2016)
What motivates some linguistic minorities to maintain their language? Why do others shift away from it rather quickly? Are there specific conditions - environmental or personal - influencing these dynamics? What can families and communities do to pass on their'threatened' language to the next generation? These and related questions are investigated in detail in Language Maintenance and Shift. In this fascinating book, Anne Pauwels analyses the patterns of language use exhibited by individuals and groups living in multilingual societies, and explores their efforts to maintain their heritage or minority language. She explores the various methods used to analyse language maintenance, from linguistic demography to linguistic biography, and offers guidance on how to research the language patterns and practices of linguistic minorities around the world.
Machine generated contents note: Introduction; Part I. History, Concepts, Contexts and Approaches: 1. Pioneers in the study of language maintenance and language shift; 2. Concepts, contexts and approaches to the study of language maintenance and shift; Part II. Investigating Language Maintenance and Shift: Collecting and Analysing Data: 3. Linguistic demography: census surveys; 4. Reporting language use and exploring language attitudes: questionnaires; 5. Beyond surveys: interviews, participant observation and experiments; Part III. Identifying and Understanding Trends and Patterns in the Dynamics of Language Maintenance and Shift: 6. Trends and patterns in language maintenance and shift; 7. Understanding the dynamics of language maintenance and shift; Part IV. Language Maintenance Efforts and Reversing Language Shift: 8. Efforts, agencies and institutions for language maintenance; 9. Reversing language shift; Part V. Future Developments in the Study of Language Maintenance and Shift: 10. Opportunities and challenges for the future study of language maintenance and shift.
Title from publisher's bibliographic system (viewed on 08 Aug 2016).
Keywords: Language maintenance -- Research; Linguistic change -- Research; Linguistic minorities -- Research; Code switching (Linguistics); Sociolinguistics